Pengaruh Pendidikan Kesehatan dengan Metode Ceramah Terhadap Tingkat Pengetahuan Remaja Tentang Penyakit Menular Seksual di Fase-E SMA Cahaya Sakti - Fatimah, Amalia; Rostarina, Nila; Achirman; Eka Ramadhan, Gaung (STIKES Ngesti Waluyo, 2024)
Sexually transmitted infections are diseases that are transmitted through sexual intercourse. Infectious infections can be at greater risk when engaging in relationships with changing partners either vaginally, orally, or anally. According to WHO, adolescents are the population in the age range of 10 to 18 years. Adolescents are very at risk of sexually transmitted infections because, in adolescence, there will be high curiosity and a lack of knowledge. Therefore, the importance of health education for adolescents in knowledge about sexually transmitted diseases. The purpose of this study was to determine the effect of health education with the lecture method on students' level of knowledge about sexually transmitted diseases. This research method uses a one group pretest- posttest design. The population in this study were all students of phase-e SMA Cahaya Sakti. The sample of this study was 30 respondents, and the sampling method used was total sampling. The instrument used in this study was a pre- and post-knowledge questionnaire sheet, and the statistical test used was Paired T-Test. The results showed that there was an effect of health education with the lecture method on students' level of knowledge about sexually transmitted diseases in adolescents (p=0.001). Based on the results of this study, it is hoped that it can be used as input for nursing services in providing health education about knowledge of sexually transmitted diseases in adolescents so that knowledge increases related to sexually transmitted infections.